Distribution and expression of type VI collagen and elastic fibers in human rotator cuff tendon tears. (October 2014) - Thakkar, Dipti; Grant, Tyler M.; Hakimi, Osnat; Carr, Andrew J.
Abstract There is increasing evidence for a progressive extracellular matrix change in rotator cuff disease progression. Directly surrounding the cell is the pericellular matrix, where assembly of matrix aggregates typically occurs making it critical in the response of tendon cells to pathological conditions. Studies in animal models have identified type VI collagen, fibrillin-1 and elastin to be located in the pericellular matrix of tendon and contribute in maintaining the structural and biomechanical integrity of tendon. However, there have been no reports on the localization of these proteins in human tendon biopsies. This study aimed to characterize the distribution of these ECM components in human rotator cuffs and gain greater insight into the relationship of pathology to tear size by analyzing the distribution and expression profiles of these ECM components. Confocal microscopy confirmed the localization of these structural molecules in the pericellular matrix of the human rotator cuff. Tendon degeneration led to an increased visibility of these components with a significant disorganization in the distribution of type VI collagen. At the genetic level, an increase in tear size was linked to an increased transcription of type VI collagen and fibrillin-1 with no significant alteration in the elastin levels. This is the first study to confirm the localization of type VI collagen, elastin and fibrillin-1 in the pericellular region of human supraspinatus tendon and assesses the effect of tendon degeneration on these structures, thus providing a useful insight into the composition of human rotator cuff tears which can be instrumental in predicting disease prognosis.